Hydrogen storage in scandium decorated triazine based g-C3N4: Insights from DFT simulations. (25th December 2022) - Chakraborty, Brahmananda; Mane, Pratap; Vaidyanathan, Antara
Abstract: Hydrogen is being considered a 'fuel of the future, ' a viable alternative to fossil fuels in fuel cell vehicles. Using Density Functional Theory simulations, reversible, onboard hydrogen storage in Sc-decorated triazine-based graphitic carbon nitride (g-C3 N4 ) has been explored. Sc atom binds strongly on the g-C3 N4 structure with a binding energy of −7.13 eV. Each Sc atom can reversibly bind 7 molecules of hydrogen, giving a net gravimetric storage capacity of 8.55 wt%, an average binding energy of −0.394 eV per H2, and a corresponding desorption temperature of 458.28 K, fulfilling the criteria prescribed by the US Department of Energy. The issue of transition metal clustering has been investigated by computing the diffusion energy barrier (2.79 eV), which may be large enough to hinder the clustering tendencies. The structural integrity of Sc-g-C3 N4 has been verified through ab-initio Molecular Dynamics simulations. The interaction mechanism of Sc over g-C3 N4 and H2 over Sc-g-C3 N4 has been explored using density of states and charge transfer analysis. A flow of charge from valence 3d orbitals of Sc towards vacant orbitals of g-C3 N4 during the binding of Sc over g-C3 N4 is observed. The binding of H2 on Sc-g-C3 N4 may be via Kubas type of interactions which is stronger than physisorption due to net charge gain by H 1s orbital from Sc 3d orbital. Our systematic investigations indicate that Sc-decorated g-C3 N4 may be a high-performance material for reversible hydrogen storage applications. Graphical abstract: Image 1 Highlights: Sc attached at stable site on g-C3 N4 with binding energy −7.13 eV. Single Sc adsorbs 7H2 molecules leading to 8.62 gravimetric wt % of hydrogen. Average desorption temperature of 458.28 K ideal for applicable range. Stability of structure evidenced from MD simulations. H2 adsorbed due to Kubas interactions with average binding energy of −0.39 eV/H2 .